1993
DOI: 10.1080/00140139308967861
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of the adaptation of circadian rhythms to rapid time zone changes

Abstract: The aim of the study was to find out which factors could explain individual differences in the resynchronization speed of circadian rhythms of salivary melatonin and subjective alertness after transmeridian flights over 10 time zones. The mean age of the 40 female subjects was 33.0 +/- 6.9 years. The data were gathered by measurements of the circadian rhythms of melatonin excretion and altertness at 2 h intervals in Helsinki (Finland) two days before westward flight to Los Angeles (USA), where the measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These studies all indicate the heterogeneity of circadian adaptation to night shift work where progressive reduction of morning cortisol levels is consistent with some degree of circadian adaptation to a night oriented schedule 15,75) . Adaptive phase delays of cortisol and melatonin rhythms to an atypical work schedule are possible 76) and are influenced by the pattern of light and darkness exposure 17,75,[77][78][79][80][81][82][83][84] . The pattern of light exposure in night shift workers who spontaneously adapt to the shift work schedule are notable for the stability of sleep times 13) , limited exposure to bright sunlight in the morning 17) , brighter light during shift hours combined with sleep times in darkness 81) , and limited exposure to light throughout the day in Antarctic studies 85) .…”
mentioning
confidence: 99%
“…These studies all indicate the heterogeneity of circadian adaptation to night shift work where progressive reduction of morning cortisol levels is consistent with some degree of circadian adaptation to a night oriented schedule 15,75) . Adaptive phase delays of cortisol and melatonin rhythms to an atypical work schedule are possible 76) and are influenced by the pattern of light and darkness exposure 17,75,[77][78][79][80][81][82][83][84] . The pattern of light exposure in night shift workers who spontaneously adapt to the shift work schedule are notable for the stability of sleep times 13) , limited exposure to bright sunlight in the morning 17) , brighter light during shift hours combined with sleep times in darkness 81) , and limited exposure to light throughout the day in Antarctic studies 85) .…”
mentioning
confidence: 99%
“…Parents of small children, for example, may have sleep and life schedules that are relatively less attuned to the clock and so be less sensitive to the clock shifts. Indeed, evidence suggests that different personality types may respond more or less dramatically to circadian-rhythm disruptions (Suvanto, Härmä, & Laitinen, 1993). And while the American calendar may be uniquely susceptible to the effects of clock shifts, other countries might see their own specific implications.…”
Section: Conclusion: It's About Timementioning
confidence: 99%
“…11 It has also been reported that re-entrainment after transmeridian flights is more rapid in summer than in winter, possibly because the longer day permits greater exposure to natural daylight. 12 Jet lag and athletic performance Some aspects of chronobiology are important to physical performance-for example, the normal cyclic variation observed in the physiological mechanisms that contribute to overall athletic performance, the eVect of abnormal rhythmicity or desynchronisation on athletic performance, and the alleviating counter measures.…”
Section: Jet Lagmentioning
confidence: 99%